A Scientometric Approach to the Taxonomy of Brazilian Plecoptera: An Overview of Data - Duarte Simoes, Tacio Vitor (2024)
The order Plecoptera comprises nearly 4,400 species of freshwater insects known for their specific temperature requirements. In Brazil, there are 207 valid extant species, with 172 (83%) being endemic, and particularly the genus Anacroneuria is well-represented. This study aims to present a comprehensive overview of the taxonomy of Brazilian Plecoptera using a scientometric approach. Initially, European authors dominated the taxonomy, describing 67 species by the mid-20th century, but Brazilian researchers, notably Claudio Gilberto Froehlich, have made significant contributions, describing 82 species. Type-specimens of Brazilian species are mostly held in Brazilian institutions, with the MZSP in São Paulo housing the majority (79.8%). São Paulo is the state with the highest number of species (67), followed by Rio de Janeiro (47) and Santa Catarina (47). The states of Alagoas, Paraíba, and Rio Grande do Norte have no recorded Plecoptera species. Among Brazilian terrestrial biomes, the Atlantic Forest exhibits the highest number of species, with 140 known species, followed by the Brazilian Savanna (57). The Hydrographic Region of Southeast Atlantic is that with the largest number of species (82). Limited data exist on the immature stages of Plecoptera across most genera, representing only a quarter of the current diversity in Brazil. Additionally, only 9.7% of the species have available molecular sequence data. Despite these challenges, the Plecoptera in Brazil demonstrate remarkable species diversity, with a significant proportion of endemism. Both European and Brazilian researchers have played crucial roles in advancing the taxonomy and understanding of this fascinating group of insects.